Exploring the association between regional fat distribution and atrial fibrillation risks: a comprehensive cohort study - Wu, Chenkai; Xu, Yuefei; Xing, Zhenhua (Frontiers in Endocrinology, 2024)
Background: The contribution of total fat mass and regional fat distribution to the risk of AF has rarely been studied. Methods: This prospective cohort study(N=494,063) evaluated the association of total fat mass measured by fat percentage (FP) and regional fat measured by arm fat percentage (AFP), trunk fat percentage (TFP), and leg fat percentage (LFP) with incident AF. A subgroup (N = 25,581) underwent MRI, which allowed us to further assess whether visceral adipose tissue (VAT) and abdominal subcutaneous adipose tissue (ASAT) of the trunk fat exert different effects on AF incidence. Results: Over, a median 12.9±1.86 years of follow-up, 29,658 participants (cumulative rate: 6.0%) developed AF. Each 1-standard deviation (SD) increase in LFP was associated with a 16% lower risk of AF (HR: 0.84, 95% CI: 0.82, 0.85). The association between FP and AF was weaker than that between LFP and AF (HR: 0.90, 95% CI: 0.89, 0.92). AFP and TFP only had a marginal association with a lower incidence of AF. Both the VAT and ASAT showed a U-shaped relationship with incident AF. Conclusions: Fat mass, mainly leg fat mass, was associated with a lower risk of AF. ASAT did not exert protective effects.